2021
DOI: 10.1037/adb0000718
|View full text |Cite
|
Sign up to set email alerts
|

Packing cannabis, pouring alcohol: Validating a free-pack assessment among college students using cannabis.

Abstract: Long-standing challenges in quantifying cannabis use make assessment difficult, potentially complicating attempts to minimize harm. Our study investigated how accurately undergraduates who use substances estimate amounts of alcohol through a behavioral pouring task. We also aimed to validate a free pack assessment in which participants similarly estimated amounts of cannabis. We further examined how estimations related to consequences and protective behavioral strategies (PBS). Methods: Participants completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Daily quantity of cannabis reported on MR and TLFB did not significantly predict quantity reported on EMA surveys that same day. Compared to alcohol, it is possible that cannabis quantities may be more difficult for participants to estimate, leading to more error in retrospection (Mian et al, 2021; Prince et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Daily quantity of cannabis reported on MR and TLFB did not significantly predict quantity reported on EMA surveys that same day. Compared to alcohol, it is possible that cannabis quantities may be more difficult for participants to estimate, leading to more error in retrospection (Mian et al, 2021; Prince et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies examining the prevalence of college student drinking (Bergen-Cico & Kilmer, 2010;White & Hingson, 2013), as well as the effectiveness of interventions (Hennessy et al, 2019), rely exclusively on college students' self-reports of the number of standard drinks they consumed. Given that self-report is fraught with problems of reliability and validity (Kohn et al, 2017;Mian et al, 2021), at the very least, the free-pour of a standard serving (i.e., knowledge assessment; Schultz et al, 2017) ought to be used to corroborate college students' self-reports.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies examining the prevalence of college student drinking (Bergen‐Cico & Kilmer, 2010; White & Hingson, 2013), as well as the effectiveness of interventions (Hennessy et al., 2019), rely exclusively on college students' self‐reports of the number of standard drinks they consumed. Given that self‐report is fraught with problems of reliability and validity (Kohn et al., 2017; Mian et al., 2021), at the very least, the free‐pour of a standard serving (i.e., knowledge assessment; Schultz et al., 2017) ought to be used to corroborate college students' self‐reports. Another type of free‐pour assessment, the typical drink assessment (Schultz et al., 2017), could be used to assess the amount students typically consume (Kaskutas & Graves., 2000), which could then be compared to standard servings for assessment and teaching purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Higher and lower potency was described using an alcohol analogy (e.g., Bacardi is high potency; beer is low potency) and presented as 'cannabis (that) differs in potency in that it is of higher/lower potency than what you have previously used'. The method aimed to conceptually replicate the Roll a Joint paradigm [8]. The potency manipulation was counterbalanced to control for ordering effects.…”
Section: Designmentioning
confidence: 99%
“…They found that self‐reported estimations of cannabis amount were 200% greater than the actual quantity of cannabis flower and tobacco rolled into spliffs [7]. Prince et al [4] and Mian et al [8] also found low accuracy estimates of cone and joint quantities.…”
Section: Introductionmentioning
confidence: 99%